Brand Management Nowadays - Silvia Delia OLARU; Elena GURGU (Revista de Management Comparat International)
Although the economy is expected to recover somewhat in 2010, the reality is that brands and retailers are facing - and will continue to face for a generation to come - a very different consumer. In this sense, many wise marketers and brands will seek inspiration from brands that won in the Great Depression. That period saw a generation of shoppers completely transformed. Today’s recession, the likes of which most current day consumers and marketers have never seen or felt but only heard of, has shaken shoppers to the core.